Своєрідний мікросвіт літератури для дітей на Буковині - Філіп, Ю. (Літературознавчі обрії. Праці молодих учених, 2010)
Because the world of the literature for children is created by rich poets’ imagination, it is good for growing children who according to Olena Pchilka are our treasure, the hope of our young Ukraine. Literature for children depends on children themselves and influences the destiny of a land and its future. The Bukovinians had never stood apart from these things, thus their creative attempts deserve respect.